Solidification Processing of Metallic Alloys Under External Fields - Eskin, Dmitry G.; Mi, Jiawei; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explores the application of external physical fields to the solidification processing of metallic alloys. Leading academics from around the world present comprehensive and critical reviews on state-of-the-art research and discuss possible future directions. Major physical fields, including electromagnetic, electric, acoustic, and thermal, are considered. In addition, the most advanced synchrotron X-ray based real-time and in-situ studies and numerical modeling methodologies are reviewed and discussed, with a special emphasis on their applications to the solidification processes. Throughout, all chapters are illustrated with both historical and very recent research cases, including typical examples of in-situ studies, modeling, and simulation. This book contains essential knowledge and information suitable for a wide audience, from undergraduate and postgraduate students to academics, practicing researchers, and engineers in materials, metallurgy, and manufacturing. Presents state-of-the-art research in an important and fast-growing field Covers fundamental theory, real-time characterization, modeling, and applications Features a combination of original results and systematic review of published literature by the leading researchers in the world Represents a comprehensive reference for researchers and engineers working in materials processing.
List of Contributors -- 1 Basics of solidification processing of metallic alloys -- 2 In-situ studies of the dynamics of metal solidification -- 3 Magnetohydrodynamics processing and modelling -- 4 Electromagnetic stirring and low frequency electromagnetic vibration -- 5 High-frequency vibration and ultrasonic processing -- 6 High magnetic fields processing of metal alloys -- 7 Pulse external fields processing of metal alloys -- 8 Thermal melt processing of metallic alloys -- Index.
Keywords: Metals; Condensed matter; Materials; Building materials; Materials -- Analysis; Manufactures; Metals and Alloys; Phase Transitions and Multiphase Systems; Materials Engineering; Structural Materials; Characterization and Analytical Technique; Machines, Tools, Processes